Dynamika oraz kierunki zmian struktury usług produkcyjnych w rolnictwie - Kukuła, Karol (Wydział Prawa i Administracji UAM, 1986)
A development of productional services for agriculture is one of the essential factors effecting the progress in production, effectiveness and prime costs. This fact can justify advisability of the undertaken research in tendencies and directions of changes in the structures related to the productional services in agriculture. The article presents the analysis of a course of changes in the services structure in the cross-sections: sector, objective and subjective. The period of 1975 - 1983 was examined. The analysis was performed by the own method of measuring the structure dynamics. The study proves that the share of unsocialized sector in a general value of sold services constantly increases. Thus a process of nullifying differences in a dissémination of productional services between socialized and unsocialized farms is developing This tendency has to be estimated in a positive way. The most radical changes in all the structures are observed in the years 1981 - 1982, i.e. the period of substantial socio-economic changes. Among the negative tendencies one has to note a systematic decrease in the share of transport services. This tendency can be observed in both sectors. The further changes of structure of productional services in those directions which will be found favorable is related to a wide diffusion of a technological progress to the sphere of the discussed services. It calls for radical changes in the domain of allocation of funds engaged in the food economy for the sake of agricultural services, especially the specialized ones. These changes must account for the economic specificity in the particular sectors.
The Dynamics and the Direction of Changes in a Structure of Productional Services in Agriculture